2016
DOI: 10.1002/chem.201603522
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of N‐Arylsulfonimides: An Easily Available Class of Nonionic Photoacid Generators (PAGs)

Abstract: The photochemical behavior of differently substituted N-arylsulfonimides was investigated. Homolysis of the S-N bond took place as the exclusive path from the singlet state to afford both N-arylsulfonamides and photo-Fries adducts, the amount of which depended on reaction conditions and aromatic substituents. Sulfinic and sulfonic acids were released upon irradiation under deaerated and oxygenated conditions, respectively. The nature of the excited states and intermediates involved were proved by laser flash p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…The presence of methanesulfonyl groups on the gold surface is in agreement with previous studies, indicating that sulfonyl radicals (both methanesulfonyl and arylsulfonyl radicals) can be generated via photolysis of different aromatic substrates, including arylsulfonates and N -arylsulfonimides . The absence of these groups as substituents on the grafted aryl moieties is in agreement with these previous photochemical experiments where such electrophilic species poorly react with arenes bearing electron-withdrawing substituents (e.g., CH 3 CO−), while they are efficiently trapped by electron-rich aromatics.…”
Section: Resultssupporting
confidence: 91%
“…The presence of methanesulfonyl groups on the gold surface is in agreement with previous studies, indicating that sulfonyl radicals (both methanesulfonyl and arylsulfonyl radicals) can be generated via photolysis of different aromatic substrates, including arylsulfonates and N -arylsulfonimides . The absence of these groups as substituents on the grafted aryl moieties is in agreement with these previous photochemical experiments where such electrophilic species poorly react with arenes bearing electron-withdrawing substituents (e.g., CH 3 CO−), while they are efficiently trapped by electron-rich aromatics.…”
Section: Resultssupporting
confidence: 91%
“…The degree of polymerization of compound 4 is quite similar to that obtained with commercial DPST. On the contrary, trifluoromethanesulfonimide 5 exhibited a modest efficiency (see Figure c) due to its inability to release strong sulfonic acids …”
Section: Methodsmentioning
confidence: 99%
“…Recently we have demonstrated that irradiation of N ‐arylsulfonimides (e.g. 1‐5 ) in air saturated acetonitrile caused likewise the release of sulfonic acids (up to two equivalents, 200% yield, for compounds 1‐4 , Scheme ) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical structures and photochemical reaction mechanisms of non-ionic PAGs are shown in Table 1 [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Non-ionic Pagsmentioning
confidence: 99%